2017
DOI: 10.19044/esj.2017.v13n36p218
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant and Anti-Diabetic Potential of Gymnema Sylvestre Methanol Leaf Extract

Abstract: Some medicinal plants and their purified derivatives have demonstrated beneficial therapeutic potentials for many centuries. They have been reported to exhibit antioxidant activity, reducing the oxidative stress in cells and are therefore useful in the treatment of many human diseases, including diabetes and other non-communicable diseases. This study evaluated antioxidative activity and enzymatic (alpha-amylase and alphaglucosidase) inhibitory potentials of Gymnema sylvestre methanolic leaf extract (GSMLE) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…The uses of synthetic drugs in treatment of Alzheimer's disease such as galantamine and rivastigmine has undesirable side effects, including gastrointestinal troubles such as stomach pain, diarrhea, nausea, vomiting, loss of appetite leading to weight loss, watering eyes, irregular breathing, muscle weakness, and confusion (Mehta, Adem, & Sabbagh, 2012;Rösler et al, 1999). Moreover, diabetic treatment is based on carbohydrate enzymes (such as α-amylase and α-glucosidase) inhibition (Ibrahim et al, 2017;Kim, Kwon, Jang, & Kwon, 2009;Kwon, Vattem, & Shetty, 2006;Rasouli, Hosseini-Ghazvini, Adibi, & Khodarahmi, 2017) as well as other mechanisms such as reduction of glucose level and maintain of β-cells performance (Purnomo, Soeatmadji, Sumitro, & Widodo, 2017). It has been shown that the inhibition of α-amylase and α-glucosidase correlates with the increases of postprandial glucose level and reduces the absorbance of glucose in the intestine, limiting the excursion of glucose in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The uses of synthetic drugs in treatment of Alzheimer's disease such as galantamine and rivastigmine has undesirable side effects, including gastrointestinal troubles such as stomach pain, diarrhea, nausea, vomiting, loss of appetite leading to weight loss, watering eyes, irregular breathing, muscle weakness, and confusion (Mehta, Adem, & Sabbagh, 2012;Rösler et al, 1999). Moreover, diabetic treatment is based on carbohydrate enzymes (such as α-amylase and α-glucosidase) inhibition (Ibrahim et al, 2017;Kim, Kwon, Jang, & Kwon, 2009;Kwon, Vattem, & Shetty, 2006;Rasouli, Hosseini-Ghazvini, Adibi, & Khodarahmi, 2017) as well as other mechanisms such as reduction of glucose level and maintain of β-cells performance (Purnomo, Soeatmadji, Sumitro, & Widodo, 2017). It has been shown that the inhibition of α-amylase and α-glucosidase correlates with the increases of postprandial glucose level and reduces the absorbance of glucose in the intestine, limiting the excursion of glucose in plasma.…”
Section: Introductionmentioning
confidence: 99%